Annealing effects on microstructural, optical, and mechanical properties of sputtered CrN thin film coatings: Experimental studies and finite element modeling - Ibrahim, K.; Rahman, M.; Zhao, X.; Veder, Jean-Pierre; Zhou, Z.; Mohammadpour, E.; Majeed, R.; Nikoloski, A.; Jiang, Z. (Elsevier B.V., 2018)
© 2018 Elsevier B.V. Chromium nitride (CrN) coatings were deposited by magnetron sputtering onto Si(100) substrates. The coatings were then annealed at different temperatures (500–800 °C in steps of 100 °C) in air for 1 h. X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), X-ray photoelectron spectroscopy (XPS), UV–Vis spectroscopy, nanoindentation tests and finite element modeling (FEM) were conducted in order to investigate their structural, morphological, optical and mechanical properties. XRD patterns show that the crystallinity of the CrN phase increases with the rise in annealing temperatures together with its preferred orientations along (111) and (200) diffraction planes. The lattice constants were slightly reduced from 4.19 to 4.11 nm at 800 °C. The lattice micorstrains and residual stresses were also reduced as the annealing temperatures rose as a result of reduced defects, dislocations and vacancies. Smooth grain-like surfaces with grain sizes ranging between ~50 and 250 nm were confirmed by FESEM micrographs. XPS studies indicated the existence of Cr and N on the coating systems. Optical studies showed that with the rise in annealing temperature of up to 700 °C, the solar absorptance of CrN coatings is increased from 61% to 89% and slightly decreased at 800 °C, while the optical band-gap energy dropped from 2.62 to 1.38 eV and slightly increased to 1.48 eV at 800 °C. A gradual increase of dielectric constants of CrN films were realized with the subsequent annealing progression. Nanoindentation results indicated that as the annealing progresses, the hardness and elastic modulus values are lowered.